Identifying therapeutic elements of islamic spiritual nursing education to reduce depression in patients with coronary artery disease: A delphi study - Aan Nuraeni; Suryani Suryani; Yanny Trisyani; Yulia Sofiatin; Helmy Hazmi; Sheizi Pristasari (Jurnal Keperawatan Padjadjaran, 2026)
Introduction: Patients with coronary artery disease (CAD) face a higher risk of depression, which negatively affects their quality of life. For Muslim patients, culturally and religiously sensitive interventions are crucial. Islamic-based psychotherapy shows promise, but further research is needed to determine the most effective content. This study aims to achieve expert consensus on the therapeutic components of Islamic nursing spiritual education to alleviate depression in CAD patients. Methods: The Delphi method was used, with three rounds of data collection from Muslim healthcare professionals experienced in Islamic-based care. The first round gathered qualitative insights through open-ended questions. Rounds two and three used Likert-scale assessments to evaluate the relevance and urgency of proposed topics. Consensus was defined as ≥90% agreement among the experts, with stable central tendency values and declining input indicating strong consensus. In Phase 4, we qualitatively evaluated the final consensus on therapeutic strategies with patients to gather their perspectives and inform potential program adaptations. Results: Seven key themes emerged, including the Islamic view on health and illness, the prophetic guidance of Prophet Muhammad SAW regarding illness, and the role of faith, gratitude, and worship in mental well-being. Over 90% agreement was achieved across all themes, with mean relevance scores ranging from 3.8 to 4.0 and urgency scores from 3.7 to 4.0, confirming consensus stability. Patients validated the content, noting its potential to reduce anxiety and fear. Conclusions: Integrating Islamic spiritual education into psychotherapeutic interventions could help address depression among Muslim CAD patients. Further studies are needed to evaluate its clinical effectiveness.